Municipal solid waste generation in Algarve, Portugal: Challenges of seasonal tourism - Magro, C.; Roseta-Palma, C.; Dionísio, J.; Mota, J.; Almeida, C. R. de.; Cardadeiro, E. (European Review of Business Economics, 2025)
Regions with strong tourism seasonality, like Portugal’s Algarve, face major challenges in municipal solid waste (MSW) management. This study quantifies tourism-induced waste using data from 2017–2024, in collaboration with Algar, the regional MSW utility. In 2024, the Algarve experienced six times more overnight stays in high season than low season, accounting for 25% of Portugal’s total. Yet only 9 of its 16 municipalities host 76% of residents and 95% of overnight stays. Regression models reveal strong links between tourism and waste generation. Tourists produce an estimated 3.44 kg of MSW per overnight stay—double a resident’s daily output—with 3.1 kg unsorted and glass waste four times higher than that of residents. Although tourism accounts for only 27% of annual MSW, it drives over 41% of capacity needs due to seasonality. Findings support fairer, data-driven cost-sharing and system improvements to more effectively manage waste.